Thermoplastic Intumescent Coatings Modified with Pentaerythritol-Occluded Carbon Nanotubes - Michał Tomczak (MDPI AG, 2021)
A thermoplastic intumescent coating system (IC) based on poly(vinyl acetate) was modified by two forms of multiwalled carbon nanotubes (CNTs), i.e., by a nanofiller powder and its solid dispersions in pentaerythritol (PER-CNTs). It was revealed that only the PER-CNTs modifier allows us to obtain solvent-borne ICs with a relatively high CNTs concentration (1–3 wt. parts of CNTs/100 wt. parts of paint solids) and acceptable application viscosity. Thermal insulation time (TIT) and intumescent factor (IF) of the ICs on a steel substrate (a fire test according to a cellulosic fire curve), as well as morphology, chemical structure (by the FT-IR technique) and mechanical strength of the charred systems, were investigated. It was found that the CNTs powder decreases TIT and IF values while PER-occluded CNTs improve these parameters (e.g., +4.6 min and +102% vs. an unmodified sample, respectively). Compressive strength of the charred ICs was improved by the PER-CNTs modifier as well.